2018
DOI: 10.1186/s40478-018-0599-9
|View full text |Cite
|
Sign up to set email alerts
|

The susceptibility of cochlear outer hair cells to cyclodextrin is not related to their electromotile activity

Abstract: Niemann-Pick Type C1 (NPC1) disease is a fatal neurovisceral disorder caused by dysfunction of NPC1 protein, which plays a role in intracellular cholesterol trafficking. The cholesterol-chelating agent, 2-hydroxypropyl-β-cyclodextrin (HPβCD), is currently undergoing clinical trials for treatment of this disease. Though promising in alleviating neurological symptoms, HPβCD causes irreversible hearing loss in NPC1 patients and outer hair cell (OHC) death in animal models. We recently found that HPβCD-induced OHC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 57 publications
3
13
0
Order By: Relevance
“…However, the high doses of cyclodextrins needed to ameliorate NPC1 generally lead to high-frequency hearing loss. Studies of ototoxicity in cats and mice indicate that HPβCD mainly damages the outer hair cells (OHC) while sparing the inner hair cells (IHC) and spiral ganglion neurons (SGN) (Cronin et al, 2015, Crumling et al, 2017, Crumling et al, 2012, Takahashi et al, 2016, Ward et al, 2010, Zhou et al, 2018. Because the electromotile OHC provide the auditory system with its exquisite sensitivity and sharp tuning, the selective destruction of OHC by HPBCD results in a significant hearing loss (Liberman et al, 2002, Ryan andDallos, 1975).…”
Section: Introductionmentioning
confidence: 99%
“…However, the high doses of cyclodextrins needed to ameliorate NPC1 generally lead to high-frequency hearing loss. Studies of ototoxicity in cats and mice indicate that HPβCD mainly damages the outer hair cells (OHC) while sparing the inner hair cells (IHC) and spiral ganglion neurons (SGN) (Cronin et al, 2015, Crumling et al, 2017, Crumling et al, 2012, Takahashi et al, 2016, Ward et al, 2010, Zhou et al, 2018. Because the electromotile OHC provide the auditory system with its exquisite sensitivity and sharp tuning, the selective destruction of OHC by HPBCD results in a significant hearing loss (Liberman et al, 2002, Ryan andDallos, 1975).…”
Section: Introductionmentioning
confidence: 99%
“…In adult rats, the 4,000 mg/kg dose of HPβCD completely eliminated the DPOAE 2-days post-treatment ( Liu et al, 2020 ). Although several mechanisms have been suggested ( Crumling et al, 2017 ), selective cyclodextrin ototoxicity is believed to be correlated with prestin expression in OHCs because knockout mice missing this protein are more resistant to cyclodextrin damage than wild type mice ( Takahashi et al, 2016 ) or mutant mice with a non-electromotile form of prestin ( Zhou et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Much of the previous literature on HPβCD ototoxicity in mice has focused on its early, selective destruction of OHCs with little evidence of damage to IHCs, ANFs, or SGNs ( Crumling et al, 2012 , 2017 ; Takahashi et al, 2016 ; Zhou et al, 2018 ). However, recent studies from our lab have revealed that HPβCD unexpectedly causes massive, delayed degeneration of rat IHCs, PCs, ANFs, SGNs, and much of the organ of Corti ( Ding et al, 2020 ; Liu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms of the selective damage to OHCs remain undetermined. One factor at plays may be that prestin, the OHC motor protein and the main component of the OHC lateral membrane, is sensitive to changes in cholesterol levels (131)(132)(133). Compared to AABs' protocols, HPβCD seems to be a more effective agent to induce loss of OHCs selectively.…”
Section: -Hydroxypropyl-β-cyclodextrinmentioning
confidence: 99%